Progressive alteration of murine bladder elasticity in actinic cystitis detected by Brillouin microscopy - Laura Martinez-Vidal; Claudia Testi; Emanuele Pontecorvo; Filippo Pederzoli; Elisa Alchera; Irene Locatelli; Chiara Venegoni; Antonello Spinelli; Roberta Lucianò; Andrea Salonia; Alessandro Podestà; Giancarlo Ruocco; et al. (Scientific Reports, 2024)
Abstract Bladder mechanical properties are critical for organ function and tissue homeostasis. Therefore, alterations of tissue mechanics are linked to disease onset and progression. This study aims to characterize the tissue elasticity of the murine bladder wall considering its different anatomical components, both in healthy conditions and in actinic cystitis, a state characterized by tissue fibrosis. Here, we exploit Brillouin microscopy, an emerging technique in the mechanobiology field that allows mapping tissue mechanics at the microscale, in non-contact mode and free of labeling. We show that Brillouin imaging of bladder tissues is able to recognize the different anatomical components of the bladder wall, confirmed by histopathological analysis, showing different tissue mechanical properties of the physiological bladder, as well as a significant alteration in the presence of tissue fibrosis. Our results point out the potential use of Brillouin imaging on clinically relevant samples as a complementary technique to histopathological analysis, deciphering complex mechanical alteration of each tissue layer of an organ that strongly relies on mechanical properties to perform its function.